Arquitetura vernácula: registro e análise do uso do adobe em Lapinha da Serra, Santana do Riacho, Minas Gerais - Samara Luiza Santos Amancio (2018)
The main objective of the present study is to record and analyze the presence of the vernacular technique in adobe in Lapinha da Serra, Santana do Riacho MG, Brazil. Despite the lack of knowledge and fear in society regarding the use of adobe in construction, this technique has added great value in resolving cultural, social, economic and environmental issues. The scientific methodology used in this research is based on the work of Carter and Cromley (2005), which starts from the analysis of buildings for later understanding of the whole set. When analyzing the context where Lapinha da Serra is inserted, it is noticed that there is a significant growth of the village due to the tourism, ratifying the importance and the need for conservation of the local cultural patrimony. Specifically, it has carried out data collection and survey of buildings for comparative parametric analysis, with presentation of maps, aiming to affirm the stylistic and epistemological importance of the vernacular architecture. Note not only the availability of the record of the techniques of the master craftsmen who worked there but also the great importance of the registration and survey of the buildings in the district of Lapinha da Serra. This result is important to safeguard the current scenario of the adobe technique, should it ever disappear in the district. It is anticipated that the results of this work could awaken the positioning of public policies that will take into account the academic vision thus making it possible to draw up strategies that guarantee the preservation of cultural heritage, its valorization, and its incentive to the continuity of the technique in adobe by the local community.